Intricately carved pillar - Temples of India Project Team (Jio Institute, 2024)
Extant pillar from what was likely a torana (decorative arch) that must have been part of the archway on the northern side of the temple. The pillar is intricately carved based on a multi-moulding plinth in which the base has a row of elephants, or the gajathara (elephant band). The lower shaft of the pillar has three sets of sculptures, and the topmost part of the shaft has two brackets. The torana must have been attached to the bracket remains on the pillar.